Triple negative breast cancer subtypes and pathologic complete response rate to neoadjuvant chemotherapy. - Santonja, Ángela; Sánchez-Muñoz, Alfonso; Lluch, Ana; Chica Parrado, María del Rosario; Albanell, J.; Chacón, José Ignacio; Antolín, Silvia; Jerez-Aragonés, José Manuel; De la Haba, Juan; De Luque, Vanessa; Fernández-De-Sousa, Cristina Elisabeth; Vicioso-Recio, Luis Prudencio; et al. (Impact Journals, 2018)
Triple negative breast cancer (TNBC) is a heterogeneous disease with distinct molecular subtypes that differentially respond to chemotherapy and targeted agents. The purpose of this study is to explore the clinical relevance of Lehmann TNBC subtypes by identifying any differences in response to neoadjuvant chemotherapy among them. We determined Lehmann subtypes by gene expression profiling in paraffined pre-treatment tumor biopsies from 125 TNBC patients treated with neoadjuvant anthracyclines and/or taxanes +/- carboplatin. We explored the clinicopathological characteristics of Lehmann subtypes and their association with the pathologic complete response (pCR) to different treatments. The global pCR rate was 37%, and it was unevenly distributed within Lehmann’s subtypes. Basal-like 1 (BL1) tumors exhibited the highest pCR to carboplatin containing regimens (80% vs 23%, p=0.027) and were the most proliferative (Ki-67>50% of 88.2% vs. 63.7%, p=0.02). Luminal-androgen receptor (LAR) patients achieved the lowest pCR to all treatments (14.3% vs 42.7%, p=0.045 when excluding mesenchymal stem-like (MSL) samples) and were the group with the lowest proliferation (Ki-67≤50% of 71% vs 27%, p=0.002). In our cohort, only tumors with LAR phenotype presented non-basal-like intrinsic subtypes (HER2- enriched and luminal A). TNBC patients present tumors with a high genetic diversity ranging from highly proliferative tumors, likely responsive to platinum-based therapies, to a subset of chemoresistant tumors with low proliferation and luminal characteristics.
Este articulo ha sido publicado en la revista Oncotarget. Esta versión tiene Licencia Creative Commons CC-BY
Keywords: Cáncer - Tratamiento; Carcinogénesis; Quimioterapia; Triple negative; Breast cancer; Pathologic complete response; Neoadjuvant chemotherapy